The nature and problems of the individualized instruction program at Claret School of Quezon City - Mateos, Julian Sanchez, Father 1934-
This study focuses on the implementation of the Individualized Instruction in the Claret School of Quezon City. The Claret School is a young school which started in the school year 1967-1968. The implementation of the program was started in the school year 1973-1974 and at present involves thirteen classes. This paper studied the nature of the individualized instruction applied in the school and the problems encountered during implementation.